Parental role in children's road safety experiences. (April 2017) - Muir, Carlyn; O'Hern, Steve; Oxley, Jennie; Devlin, Anna; Koppel, Sjaan; Charlton, Judith L.
Highlights: Investigated parents' understanding of their role in their child's road safety skills. Only 77% believed they were their child's primary learning source for road safety. The remaining 23% thought school, friends or television were more important. Parents with an internal locus of control typically had greater road safety knowledge. Abstract: This study investigated parents' attitudes, knowledge and behaviours relating to their role in protecting and teaching their young children road safety skills; and in particular parents' perceptions regarding where they thought their child learnt the most about road safety. A questionnaire exploring attitudes, knowledge and behaviours on general road safety was completed by 272 participants with at least one child aged between 3 and 10 years residing in the Australian state of Victoria. Participants were predominantly female (74%); were either married or in a de facto relationship (92%); and had completed secondary school education (73%). General road safety behaviours and attitudes were fairly positive, with most participants reporting that they restrict their alcohol consumption or do not drink at all while driving (98%), they drive at or below the speed limit (85%) and 'always' wear their seatbelts (98%). However, more than half of the participants reported engaging in distracting behaviours 'sometimes' or 'often' (54%) and only half reported never engaging in aggressive driving (49%). Only 77% believed they were their child's primary learning source for road safety skills (internal locus of control). The remaining 23% believed school, friends or television were the primary source (external locus of control). Parents with an internal locus of control in educating their children about road safety skills were significantly more likely to be educated at a University level or higher and were more likely to reside in metropolitan versus rural/regional areas, compared with parents with an external locus of control. Parents with an internal locus of control typically had greater knowledge about: whether it is legal in Victoria to drive with unrestrained passengers; whether fines were intended for revenue raising; and whether it is OK to drive 10 km/h above the speed limit in some circumstances. This research provides evidence for road safety intervention development, particularly the potential for parents to be the primary trainers in road safety skills.